Smart Shopping Carts: How Real-Time Feedback Influences Spending. (November 2013) - van Ittersum, Koert; Wansink, Brian; Pennings, Joost M.E.; Sheehan, Daniel
Although interest in smart shopping carts is increasing, both retailers and consumer groups have concerns about how real-time spending feedback will influence shopping behavior. Building on budgeting and spending theories, the authors conduct three lab and grocery store experiments that robustly show that real-time spending feedback has a diverging impact on spending depending on whether a person is budget constrained ("budget" shoppers) or not ("nonbudget" shoppers). Real-time spending feedback stimulates budget shoppers to spend more (by buying more national brands). In contrast, this feedback leads nonbudget shoppers to spend less (by replacing national brands with store brands). Furthermore, smart shopping carts increase repatronage intentions for budget shoppers while keeping them stable for nonbudget shoppers. These findings underscore fundamental unexplored differences between budget and nonbudget shoppers. Moreover, they have key implications for both brick-and-mortar and online retailers as well as app developers.